Correlation between soil environment and yield and quality of Sharen (Amomi Fructus) under different planting patterns - Yin Cuiyun; Li Yihang; Yu Jing; Zhao Hongyou; Deng Zhaoyou; Tang Deying; Aung Kyaw Oo; Zhang Lixia (KeAi Communications Co., Ltd., 2023)
Objective: To study the effects of soil environment on the growth, yield, and quality of Sharen (Amomi Fructus) under different planting patterns. Methods: Soil physical and chemical indices and enzyme activities in four periods including early flowering (March), full flowering (June), fruit ripening (September), and late fruit picking (December), were measured under three planting patterns including natural forest, greenhouse, and rubber forest in Xishuangbanna, China. The changes in soil indices during the growth periods of Sharen (Amomi Fructus) under different planting patterns were analyzed, and the differences in plant growth, yield, and quality under different planting patterns were explored. Pearson correlation analysis was used to analyze the relationship between soil indices and Sharen (Amomi Fructus) growth, yield, and quality. Principal component analysis was used to investigate the effects of soil environment under different planting patterns on Sharen (Amomi Fructus) growth, yield, and quality. Results: The soil moisture, available potassium content, and urease activity of the three planting patterns of Sharen (Amomi Fructus) increased initially and decreased afterwards throughout the year; pH and organic matter content showed little change in the whole year. Exchangeable manganese content and acid phosphatase activity gradually increased throughout the year. Hydrolyzed nitrogen content, exchangeable calcium content, available zinc content, protease activity, and sucrase activity decreased initially and increased afterwards throughout the year. Exchangeable magnesium content, available iron content, and catalase activity decreased annually. Total nitrogen content, total phosphorus content, and available phosphorus content fluctuated throughout the year. The total potassium content under natural forest and greenhouse planting decreased throughout the year, while the total potassium content under rubber forest showed an upward trend all year round. The organic matter content, total nitrogen content, total potassium content, available potassium content, available zinc content, urease activity, acid phosphatase activity, and catalase activity under greenhouse were significantly lower than those under natural and rubber forests (P < 0.05). Correlation analysis showed that plant growth, yield, and quality of Sharen (Amomi Fructus) were significantly correlated with soil organic matter, total nitrogen, hydrolyzed nitrogen, total phosphorus, available phosphorus, total potassium, available potassium, exchangeable manganese, exchangeable magnesium, exchangeable calcium, available zinc, urease, acid phosphatase, and invertase (P < 0.05). The results of the principal component analysis indicated that the soil environment of Sharen (Amomi Fructus) under natural forest was the best, followed by rubber forest and greenhouse. The order of its advantages and disadvantages is consistent with the growth index of Sharen (Amomi Fructus), but contrary to the yield of Sharen (Amomi Fructus), indicating that the soil environment directly affects the growth index and nutritional components of plants. Conclusion: Different planting patterns of Sharen (Amomi Fructus) have different soil nutrient content, and the change rules in the growths period are not similar, with some differences. Soil indices have impacts on plant growth, yield, and quality of Sharen (Amomi Fructus). Soil ecological environment is positively correlated with the growth characteristics of Sharen (Amomi Fructus) plants, but has no direct correlation with yield and quality.